NATIONAL SPECIFICS OF GESTURES AND HABITS IN ENGLISH AND UZBEK CULTURES - Kamolova Rushana Ibodovna; Yusupova Shoira Botirovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the national specifics of gestures and habits in English and Uzbek cultures. It analyzes how non-verbal communication and everyday behaviors  reflect  deeper  cultural  values  such  as  individualism,  collectivism, hospitality, and politeness. By comparing the similarities and differences between these two cultures, the article emphasizes the importance of cultural awareness in promoting effective  intercultural  communication.  The  study  concludes  that  understanding gestures  and  habits  can  bridge  cultural  gaps  and  enhance  social  interaction  in  a globalized world.